Weak ferromagnetism and superparamagnetic clusters coexistence in YFe1−xCoxO3 (0 ≤ x ≤ 1) perovskites - Pomiro, F. (2017)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina